Dyskusja na temat reformy ustroju Polskiej Rzeczypospolitej Ludowej w latach 1956-1957 - Mażewski, Lech (Czasopismo Prawno-Historyczne, 2010)
The discussion on the reforms of the political system of the Polish People's Republic that was going on in the years 1956-1957 was "chaotic, highly emotional and occasionally demagogic" (Andrzej Burda). The proposals of reforms lacked coherence and were by no means a comprehensive system of views on what the political system of the Polish State should be like. And yet, it was then when practically all possible political-legal institutions were deliberated and at least briefly considered as potential solutions, and some were returned to in subsequent political debates or reflected in the amended Constitution of 1952. The very fact that such a variety of different options was discussed despite the populist opinions praising the fundamental act on the political system then binding in Poland was in itself a positive feature, the basic weakness of the discussion, however, lay in the fact that participants in the debate did not realise the importance of a framework for the post-totalitarian system in which Poland was to function after the transformations of 1956.